Guizhi Fuling Capsule inhibits uterine fibroids growth by modulating Med12-mediated Wnt/β-Catenin signaling pathway. (23rd May 2022) - Chen, Linwei; Chen, Honglin; Yang, Qiaowei; Jiang, Yong; Liu, Lunyuan; Yu, Hui; Chen, Yan; Li, Jindong; Chen, Nan; Wang, Hua; Wang, Qin
Abstract: Ethnopharmacological relevance: Guizhi Fuling Capsule (GFC) is a famous traditional Chinese medicine (TCM) formula recorded in Synopsis of the Golden Chamber, which has achieved obvious effects in the treatment of uterine fibroids (UFs). Aim of study: Mediator complex subunit 12 (Med12) mutations were closely related to UFs in 85% of fibroid cases. The Wnt/β-Catenin signaling pathway plays an important role in the occurrence and development of UFs. This study aims to explore the pharmacological mechanism of GFC against UFs in which the Med12-mediated Wnt/β-Catenin pathway is involved. Materials and methods: Med12 was silenced in uterine fibroid cells (UFCs) using a lentivirus-based Med12 gene-specific RNA interference (RNAi) strategy. Cell proliferation was performed by CCK-8 assay, cell apoptosis and cell cycle were measured by flow cytometry. The rat model of UFs was established by injecting estradiol benzoate and progesterone. Forty-eight rats were divided into six groups, the low-dose GFC (L-GFC) group, the medium-dose GFC (M-GFC) group and the high-dose GFC (H-GFC) group were intragastrically treated with GFC solution at 0.25 g/kg, 0.50 g/kg and 1.00 g/kg per day for 8 weeks, the positive control (PC) group was administrated with mifepristone (2.70 mg/kg/day), the normal control (NC) group and the model control (MC) group were given equal volume of normal saline once a day for 8 weeks. The histopathological changes of uterine tissues were evaluated by H&E staining. The expression of Med12 in uterine tissues were detected by immunohistochemistry. The protein and mRNA levels of associated genes were evaluated by western bolt and real time-PCR, respectively. Related indicators involved in Wnt/β-Catenin pathway, such as Wnt1, β-Catenin, Cyclin D1, TCF1/TCF7 and C-myc, were compared among different groups. Results: The Wnt/β-Catenin signaling pathway was inhibited after Med12 gene was knocked out in UFCs. GFC-containing serum could induce cell apoptosis, make the cell cycle stagnated in G0/G1 phase to inhibiting the proliferation and reduce the expression of Wnt1, β-Catenin, Cyclin D1, TCF1/TCF7, and C-myc in control-shRNA cells, while had no significant effect on Med12-shRNA cells. Compared with the MC group, the weight, endometrial thickness, and pathological structure of the uterus in the GFC treated groups were significantly improved. The expression of Med12, Wnt1, β-Catenin, Cyclin D1, TCF1/TCF7, and C-myc that related to Wnt/β-Catenin pathway in the GFC treated groups were decreased with the increase of dosage administration. Conclusions: GFC inhibited UFs growth, which was directly associated with Med12 modulated Wnt/β-Catenin signaling pathway. This study provided new perspective to understand the therapeutic mechanism of UFs. Graphical abstract: Image 1 Highlights: Guizhi Fuling Capsule (GFC) inhibited the proliferation of uterine fibroid cells by disrupting the normal Med12 expression. GFC induced apoptosis and made the cell cycle stagnated in G0/G1 phase of uterine fibroid cells. GFC improved the weight, endometrial thickness, and pathological structure of the uterus in uterine fibroids model rats. GFC regulated the Med12-mediated Wnt/β-Catenin pathway to treating uterine fibroids in model rats.